Başlangicindan harf devrimine kadar Osmanli-Türk süreli yayinlar ve gazeteler bibliyografyasi ve toplu kataloğu, 1828-1928 = . Bibliography and union catalogue of Ottoman-Turkish serials and newspapers from beginning to the introduction of the modern Turkish alphabet, 1828-1928 (Enformasyon ve Dokümantasyon Hizmetleri Vakfi, 2000)
1. A-N